A Simple Fecal Bacterial Marker Panel for the Diagnosis of Crohn’s Disease - Guo, Songhe; Lu, Yongfan; Xu, Banglao; Wang, Wan; Xu, Jianhua; Zhang, Ge (Frontiers in Microbiology, 2019)
ABSTRACT Background and Aims: Intestinal dysbiosis is implicated in the pathogenesis of Crohn's disease (CD). We evaluated fecal and sera microbial markers for clinical use in detecting CD. Methods: Fecal samples from 346 Asian subjects were collected, including 95 patients with CD, 81 patients with ulcerative colitis (UC), 65 patients with irritable bowel syndrome (IBS), and 105 healthy subjects (HS). Microbial indicators Fusobacterium nucleatum (Fn), Faecalibacterium prausnitzii (Fp) and Escherichia coli (E. coli) were identified based on a review of the literature. The relative abundance of the three bacterial markers were measured by qPCR, and two serological microbial markers (anti-Fn, anti-E. coli) were measured by ELISA. We evaluated the diagnostic performance of these microbial markers by ROC curve analysis. Results: The quantification of Fp, Fn and E. coli of fecal samples is relatively stable when stored up to 6 h at room temperature. The significant increasing abundances of Fn were accompanied by a decline of Fp in the CD group. Fn exhibited a slightly higher diagnostic value than Fp in distinguishing CD from HS (Area Under Curve, AUC = 0.841 vs.0.811) or irritable bowel syndrome (IBS) groups (AUC = 0.767 vs. 0.658), and the further combination of Fn and Fp improved the diagnostic value (HS, AUC = 0.867; IBS, AUC = 0.771). However, anti-E. coli and anti-Fn antibodies in serum did not possess diagnostic value for CD or UC. Conclusions: A combination of fecal Fn and Fp was identified as a valuable marker for CD diagnosis. A CD bacterial marker panel may provide a simple noninvasive approach to screen for CD.